Physical and biological hazards of the workplace - Stave, Gregg M.; Wald, Peter H., 1955- (John Wiley & Sons Incorporated, 2017)
"Completely updated version this classic reference covers both physical hazards and biological agents. Provides updated information on protecting workers from proven and possible health risks from manual material handling, extremes of temperature and pressure, ionizing and non-ionizing (magnetic fields) radiation, shiftwork, and more Details major changes in our understanding of biological hazards including Ebola, Chikungunya, Zika, HIV, Hepatitis C, Lyme disease, MERS-CoV, TB, and much more. All infectious diseases have been updated from an occupational health perspective Includes practical guidance on to how to set up medical surveillance for hazards and suggests preventive measures that can be used to reduce occupational diseases"--